Leucemia viral felina simultánea con otras patologías en tres casos clínicos diferentes (2011)
ABSTRACT: Feline viral leukemia (ViLeF) is a pathology commonly associated with other illnesses. We present three cases of cats with ViLeF who also exhibited other pathologies. The cause and effect relationship between leukemia and the associated pathologies is not understood. The first animal also suffered from aregenerative anemia. The second cat had breast carcinoma, and the third one had peritonitis. Symptoms, diagnosis, treatment and evolution of the patients are fully described. With this report we suggest that veterinarians consider ViLeF as a possible cause for these pathologies. More studies are needed to establish the relationship between ViLeF and other pathologies for therapeutic interventions.